Analysis The Quality Of Service And Effectiveness E-Commerce Auy Publisher Using The Method E-Servqual - Paryanti, Atik Budi; Sumarsid, Sumarsid (Agregat: Jurnal Ekonomi dan Bisnis, 2019)
This research aims to analyze the quality of the service and the effectiveness of Ecommerce. This research uses a quantitative approach. Data analysis using the pras test test validity and reliability as well as a test of normality. At this stage of the analysis of data with calculations e-servqual will get the service quality level e-Commerce and the calculation of e-Commerce It can also analyze the priority of each service attribute that needs to be fixed or not. The questionnaire will be filled is given to respondents with Nonprobability Sampling technique. This study use 46 participant. The Total value of Electronic Service Quality (TESQ) obtained from the results of the calculation of the gap between perception and expectation is positive, the results obtained are 0226. This means that the customer’s expectations of the service e-Commerce in larger AUY Publisher from the Ministry obtained this time, so that the service provided is still not satisfying customers and has not been effective (X2 ).